Fracture, Fatigue, Failure and Damage Evolution, Volume 7 Proceedings of the 2017 Annual Conference on Experimental and Applied Mechanics - Carroll, Jay.; Xia, Shuman; Beese, Alison M.; Berke, Ryan B.; Pataky, Garrett J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
Fracture, Fatigue, Failure and Damage Evolution, Volume 7 of the Proceedings of the 2017 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the seventh volume of nine from the Conference, brings together contributions to this important area of research and engineering.  Session organizers include: Jay Carroll, Shuman Xia, Allison Beese, Ryan Berke, Garrett Pataky, Samantha Daly, Kavan Hazeli, Antonios Kontsos,Omer Ozgur Capraz, Scott Grutzik, Onome Scott-Emaukpor The collection presents early findings and case studies on a wide range of areas, including:  Mechanics of Energy & Energetic Materials Vibration Effects in Fracture & Fatigue Fracture & Fatigue of Additively Manufactured Materials In Situ Techniques for Fatigue & Fracture Microscale & Microstructural Effects on Mechanical Behavior Fracture & Fatigue of Composites Integration & Validation of Models with Experiments Fracture & Fatigue in Extreme Environments Novel Experimental Methods for Fatigue and Fracture Fracture of Brittle & Ductile Materials Interfacial Fracture.
Chapter 1.Interface Mechanical Strength and Elastic Constants Calculations via Nano Impact and Nanomechanical Raman Spectroscopy -- Chapter 2.Effect of Strain Rate and Interface Chemistry on Failure in Energetic Material -- Chapter 3.Characterization of Crack Tip Plasticity in IN-617 Using Indentation and Nano-mechanical Raman Spectroscopy -- Chapter 4.The Two-Way Relationship between Residual Stress and Fatigue/Fracture -- Chapter 5.Designing Brittle Fracture Specimens to Investigate Environmentally Assisted Crack Growth -- Chapter 6.Flexible Energy Harvesting/Storage Structures for Flapping Wing Air Vehicles -- Chapter 7.The Influence of Formulation Variation and Thermal Boundary Conditions on the Near-Resonant Thermomechanics of Mock Explosives -- Chapter 8.Detecting Fatigue Crack Closure and Crack Growth Delays after an Overload Using DIC Measurements -- Chapter 9.In-situ Observation of Damage Evolution in Quasi-Isotropic CFRP Laminates -- Chapter 10.Contamination-induced Degradation/Enhancement of Interfacial Toughness and Strength in Polymer Matrix Composite Interfaces -- chapter 11.Simultaneous Extraction of Mixed-Mode Traction-Separation Relations -- Chapter 12.Damage Evolution in 304L Stainless Steel Partial Penetration Laser Welds -- Chapter 13.Cross-axis Coupling and Phase Angle Effects due to Multiaxial Vibration -- Chapter 14.Behavior of Steel-Concrete Composite Beams under Fatigue Loads -- Chapter 15.Studying the Fracture of Tropical Wood Species with the Grid Method -- Chapter 16.Generalization of Integral Parameters to Fatigue Loading in Room Temperature -- Chapter 17.Fracture Behavior of Unidirectional Composites Analyzed by Acoustic Emissions Technique.
Keywords: Mechanics, Applied; Solids; Engineering geology; Materials -- Analysis; Solid Mechanics; Geoengineering; Characterization and Analytical Technique